INFLUENCE OF PROFITABILITY, COMPANY SIZE, MANAGERIAL OWNERSHIP AND TAXES ON INCOME SMOOTHING IN VARIOUS CONSUMER GOODS SECTOR MANUFACTURING COMPANIES ON THE INDONESIA STOCK EXCHANGE PERIOD 2013-2017 - Pambudi, Januar Eky; Aulia, Triana Zuhrotun; Kimsen, Kimsen (Dynamic Management Journal, 2021)
This study aims to determine the effect of Profitability proxied by Return on Assets (ROA), company size, Managerial Ownership, and Tax to Income smoothing in various sector manufacturing companies consumer goods listed on the Indonesia Stock Exchange for the period 2013-2017. This research is a type of quantitative research. The type of data used is secondary data obtained from www.idx.co.id. The population in this study are manufacturing companies of various consumer goods listed sectors listed on the Indonesia Stock Exchange for the period 2013-2017. Data analysis using data analysis using panel data regression method using Eviews version 9.0 program. While the sample in this study was determined by using the purposive sampling method so that a total of 7 companies could be obtained for the data to be processed. The results show that partially The results of the study show that partially managerial ownership affects income smoothing. While profitability is proxied by Return on Assets (ROA), company size and tax are not beneficial to income smoothing. Keywords: Return on Assets (ROA), company size, managerial ownership, Tax,  income smoothing.